PELANGGARAN UU NO 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN YANG DILAKUKAN OLEH ANAK DI WILAYAH POLSEK RAPPOCINI KOTA MAKASSAR - Alfira Sari, Dhesi; Akbal, Muhammad; Nurfatirani, Ririn (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2019)
Abstract: This article discusses the problem of Violation of Law No. 22 of 2009 concerning Traffic and Road Transportation committed by Children in the Rappocini Police Sector in Makassar City. This study aims to determine the Violation of Law No. 22 of 2009 concerning Traffic and Road Transportation carried out by Children in the Rappocini Police Station in Makassar City by knowing the types of Traffic Violations committed by children, the factors causing children to do Traffic Violations and the efforts made by the police in handling the problem of Violations Traffic carried out by children. To achieve these objectives the researchers used data collection techniques through documentation, observation and interviews. Data that has been obtained from the results of research are processed using qualitative analysis. The results showed that: (1) there were several types of violations that were often committed by children, namely, not having a SIM, not carrying a vehicle registration license, not wearing a helmet, going against the flow, driving beyond the capacity of passengers, physically incomplete vehicles. (2) there are several factors causing children to violate traffic, namely family factors, lack of parental supervision of children in giving freedom to children to drive themselves and knowledge factors where children still do not know the rules that must be obeyed when driving and environmental factors such as as a result of the association of children. (3) efforts made by the police, namely Pre-Emictive (countermeasures), Preventive (prevention) and Repressive (Handling) efforts.Keywork: Abuse, Traffic, Children